The influence of the radial internal clearance on the dynamic response of self-aligning ball bearings. (15th May 2022) - Ambrożkiewicz, Bartłomiej; Syta, Arkadiusz; Gassner, Alexander; Georgiadis, Anthimos; Litak, Grzegorz; Meier, Nicolas
Highlights: Radial internal clearance in self-aligning ball bearings is studied, The optimal radial clearance is looked for, Recurrence-based methods are applied for the analysis of acceleration time series, The sensitivity analysis for recurrence quantificators is conducted, 3 recurrence quantificators show high sensitivity to the change of radial clearance. Abstract: In this work, we present a quantitative and qualitative analysis of the dynamic response of ball bearings dependent on radial internal clearance. We measured the vibrations of a rotating system based on self-aligning ball bearings for different clearances and rotating speeds. The analysis of vibration spectra was conducted considering a set of different recurrence indicators in order to describe the response of the bearing to the optimal clearance. It comes out that indicators have different sensitivity to the changes of the internal clearance. Few quantificators, i.e. entropy, trapping time, and recurrence period density entropy demonstrate the highest sensitivity to the change of radial clearance. The proposed quantificators are useful for real-time monitoring of operating clearance.